Efektivitas Massage Terhadap Nyeri Pada Pasien Osteoarthritis Genu - Keisha Chamellaudia Barujani; Dini Nur Alpiah (JURNAL ILMIAH NUSANTARA, 2026)
Osteoarthritis of the genu is a degenerative musculoskeletal disorder that often causes knee pain, joint stiffness, and decreased ability to perform daily activities. One non-pharmacological method applied in physiotherapy to reduce pain in this condition is massage. Massage therapy functions by stimulating soft tissue, which increases blood flow, reduces muscle tension, and decreases pain perception through neuromuscular mechanisms. This study is a literature review using the PICO approach in the PubMed, ScienceDirect, and Google Scholar databases, with the criteria of Randomized Controlled Trial articles published in the last five years. Six journals found that meet the criteria and show that massage is proven effective in reducing pain intensity, improving joint stiffness, and improving knee function in patients with osteoarthritis of the genu. Massage performed for 15 to 30 minutes, with a frequency of 2 to 3 times a week for 4 to 6 weeks, produces optimal results. It can be concluded that massage is an effective and safe non-invasive therapy to reduce pain and improve function in patients with osteoarthritis of the genu.